2012
DOI: 10.1177/0003319712470966
|View full text |Cite
|
Sign up to set email alerts
|

Critical and Acute Limb Ischemia

Abstract: Some patients with peripheral arterial disease may present with critical limb ischemia, a condition associated with high rates of morbidity and mortality. Early diagnosis and effective medical therapy and revascularization are indicated to avoid amputation and reduce mortality. Ideally, a multidisciplinary approach with collaboration between endovascular interventionist, vascular surgeons, podiatrist, infectious disease, and wound care specialist is recommended for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 63 publications
0
29
0
1
Order By: Relevance
“…PAD may be manifested as IC or CLI, the latter conferring higher risk of death and CV events (20% to 25% of patients die at 1 year, and 25% to 30% undergo JOURNAL OF VASCULAR SURGERY major amputation). 27 As a more severe or unstable state, CLI may be associated with increased matrix turnover, inflammation, and endothelial stress, which can lead to increased proteolytic activity. In agreement with a previous study showing increased levels of MMP-9 in CLI patients, 11 the current study reports significantly higher levels of MMP-10 and TIMP-1 in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…PAD may be manifested as IC or CLI, the latter conferring higher risk of death and CV events (20% to 25% of patients die at 1 year, and 25% to 30% undergo JOURNAL OF VASCULAR SURGERY major amputation). 27 As a more severe or unstable state, CLI may be associated with increased matrix turnover, inflammation, and endothelial stress, which can lead to increased proteolytic activity. In agreement with a previous study showing increased levels of MMP-9 in CLI patients, 11 the current study reports significantly higher levels of MMP-10 and TIMP-1 in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The prognosis for limb salvage is poor without revascularization as major amputation rates approach 50% and serve as an independent predictor of mortality. [4][5][6][7] In addition to advanced age and non-ambulatory status, many studies have also identified other co-morbidities as independent risk factors for increased mortality and/or major amputation in CLI patients, including heart failure (HF), end-stage renal disease (ESRD), coronary artery disease (CAD), and diabetes mellitus (DM). [8][9][10][11][12][13][14][15][16] Cardiac co-morbidities are common in CLI patients, and the prevalence of HF has been reported to be 10-40% in this population.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that two million Americans suffer from critical limb ischemia (CLI) caused by peripheral arterial disease, chronic kidney disease, and severe diabetes [13]. CLI occurs when there is a poor supply of oxygenated blood to the lower extremities of the body due to artery blockage.…”
Section: Introductionmentioning
confidence: 99%